Phraseologigal Units with an Evaluative Component in Public Speech of Modern Politicians - Zhunussova, Zhanyl N.; Nugumanova, Aliya N.; Volkova, Yana A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2024)
Under the conditions of modern realities, among linguists, there exists an interestingness in studying political texts. By transmitting the abundant information to millions of people, it is possible to have a significant impact not only on public opinion, but also to influence everyday life, relationships between individuals, and shape the behavior of a society. Phraseological units functioning in political communication are able to express a thought most vividly, carry an evaluative meaning, and have a manipulative effect on an addressee. The relevance of the study is due to the relatively weak coverage of studies of phraseology as a component of the political discursive and communicative space based on the comparative material of speeches by Russian and Kazakh politicians. The purpose of this study is to examine the phraseological units of public speech, containing an evaluative component, delivered by politicians of the two countries. The study uses a continuous sampling technique, content analysis, as well as a descriptive and analytical method. The result of the study is an analysis of distinctive features, a comparison of the appliance of political phraseology in the political space of Russia and Kazakhstan. However, it should be noted that there has not been formed a unified classification of evaluative phraseological units in political discourse. The authors of the article distinguish the regularity of separating phraseological units into negative and positive contexts, and political phraseology is most often provided in the form of the opposition good - bad // self - other . Special attention is drawn to the analysis of proverbs and sayings in political speech. The authors marked the tendency self - other opposition in political speech on a rigid axiological basis, which is associated with the opposition of good - bad . In the course of the study, we noted that Kazakh politicians are less likely to turn to the categorical assessment of others, and do not use specific subjects of political activity as opponents. The description of the methods of transformation of phraseological units on the material of public speeches makes it possible for the addressee to formulate a point of view on any subject or phenomenon, evaluate it or give it a new stylistic nuance.